EFEKTIFVITAS KOMUNIKASI WEBSITE SISTEM KOMUNIKASI DATA (SISKOMDAT) PT.PERKEBUNAN NUSANTARA V KEBUN SUNGAI BUATAN SEBAGAI MEDIA INFORMASI ONLINE KARYAWAN - Berliana Maria Purba; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Data communication system website (siskomdat) is one of the new media websites in Indonesia. Website siskomdat is not only effective as a communication tool, but also effective as a medium for disseminating information either general or specific information. One of the users who use siskomdat.ptpn5.co.id website is PT. Nusantara V artificial river gardens which this website is used as a medium for disseminating job information online. The theory used is the S-M-C-R theory, source, media, channel and resource. The purpose of this study was to determine how much the level of effectiveness of communication between PT Nusantara V artificial river gardens through the website Siskomdat.ptpn5.co.id as a medium of information.This study uses quantitative research methods, with data collection techniques namely through distributing questionnaires directly to employees of PT. Nusantara V plantation artificial river gardens with a sample number of 205 which was determined through random sampling technique. Data analysis techniques in this study used descriptive statistical techniques.The results of this study indicate that the level of communication effectiveness of PT Nusantara V artificial river gardens through the Data Communication System website (Siskomdat) as an information medium is very effective. This is seen from the results of data processing based on six indicators, each indicator reaches a scale of 3.64 on the indicator receiver (receiver), scale 3.53 on the format indicator, scale 3.53 on the timekeeping indicator (timing), scale 3 , 51 on the message source indicator (source), scaling at 3.45 on the content message indicator, and scaling 3.39 on the channel indicator (media). So that the conclusions obtained by using the average formula of all indicators is 3.50 which is included in a very effective scale range. This shows that the website Siskomdat.ptpn5.co.id is a very effective media as a medium for the dissemination of job information at PT. Nusantara V plantation artificial river gardens.